Islamisasi Ilmu Pengetahuan - La Adu; Bahaking Rama; Muhammad Yahdi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
The idea of Islamization of science is a phenomenon of modernity that emerges as a response to the development of modern knowledge in the dominance of non-Islamic Western civilization. The dominance of secular civilization becomes the dominant factor in the decline of the Islamic ummah, whereas in the early history of its development, Muslims were able to prove themselves as a center of civilization and scientific growth. The advancement of science in the Islamic world continues to fade along with the decline of Islamic political power, while the rapid progress in the West indirectly has positive implications for the Islamic world. Based on this awareness, Islam undergoes a new dynamic through the reorientation and transformation of its teachings. Islamic thinkers make a breakthrough by integrating general sciences and religious sciences that we are familiar with, known as the Islamization of science. The Islamization of science is done by Islamizing the entire discipline with the fundamental essence of Islam (belief/monotheism) as its core, rather than simply adopting the secular, materialistic, and empirical nature of Western science